Use and linguistic realisations of metadiscourse features in business news - Hooi, Chee Mei; Yong, Mei Fung; Tan, Helen (Universiti Putra Malaysia Press, 2018)
Metadiscourse features are the way in which writers express their opinion and achieve not only coherence but also cohesion in their texts. Although metadiscourse features are widely employed, it is sometimes the case that writers tend to use them inappropriately, resulting in incoherent and ineffective texts. A review of the relevant literature reveals that a significant body of research has been conducted on metadiscourse features in various academic contexts. However, studies targetted at news settings are still limited. Hence, this study adapts Dafouz-Milne's model to identify the types, functions and linguistic realisations of metadiscourse features that are commonly used in business news. Quantitative data were collected from 15 business news articles from "Star Online" and "Focus Malaysia", respectively from September 2014 until June 2016. Semi-structured interviews were conducted with six business news writers individually. This paper aims to compare textual and interpersonal functions and their linguistic realisations to see whether business news in "Star Online" or "Focus Malaysia" has more engaging content to create awareness for writers.